2015
DOI: 10.1136/neurintsurg-2015-011687
|View full text |Cite
|
Sign up to set email alerts
|

Association of thrombelastographic parameters with post-stenting ischemic events

Abstract: NCT01925872.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…There was no significant difference in the correlation coefficients (p = 0.83), indicating that MA-ADP and percentage of ADP inhibition were similarly well correlated with the PRU result. Previous nonrandomized studies in cardiac surgery 12 and endovascular neurosurgery 13,14 have demonstrated an MA-ADP of 50 mm as an upper safe threshold above which thromboembolic complications are more likely. No studies of TEG have demonstrated a safe lower threshold, but a lower limit of 70 PRU has been demonstrated as a safe threshold below which hemorrhage is more likely in patients undergoing PED placement in one nonrandomized study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference in the correlation coefficients (p = 0.83), indicating that MA-ADP and percentage of ADP inhibition were similarly well correlated with the PRU result. Previous nonrandomized studies in cardiac surgery 12 and endovascular neurosurgery 13,14 have demonstrated an MA-ADP of 50 mm as an upper safe threshold above which thromboembolic complications are more likely. No studies of TEG have demonstrated a safe lower threshold, but a lower limit of 70 PRU has been demonstrated as a safe threshold below which hemorrhage is more likely in patients undergoing PED placement in one nonrandomized study.…”
Section: Resultsmentioning
confidence: 94%
“…Our trend line analyses have demonstrated a strong correlation between MA-ADP and percentage of ADP inhibition, indicating that either of these tests can be used going forward for assessment of platelet inhibition. We favor the MA-ADP, as this has been more rigorously tested with respect to thromboembolic complications in the neuroendovascular literature from China, 13,14 and because the percentage of ADP inhibition is a mathematically derived value that depends on a patient's baseline coagulation profile. In principle, there could be a patient whose baseline platelet function is on the lower end of normal who might have a therapeutic MA-ADP with a relatively low percentage inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…MA ADP reflects platelet activity to ADP-induced clot strength and assesses an individual patient's response to antiplatelet therapy. So MA ADP can potentially be used to determine patient-tailored antiplatelet therapy 16 19. However, the cut-off point of MA ADP is controversial,16 17 19 so we did not divide patients into case and control groups according to the MA ADP value.…”
Section: Discussionmentioning
confidence: 99%
“…The antiplatelet effect can be evaluated by TEG, and TEG parameters, specifically ADP-induced platelet–fibrin clot strength (MA ADP ), are associated with subsequent ischaemic events in patients with extracranial or intracranial stents 16. Quantitative assessment of MA ADP may serve as a tool to investigate individualised antiplatelet treatment designed to reduce ischaemic events 17.…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated that the TEG MA parameters might be better than light transmittance aggregometry, which ignores the important contribution of platelet–fibrin interactions to both thrombosis and hemorrhage 28. Wang et al 29 found that the ADP inhibition was lower and MA-ADP was higher in patients with ischemic events, and demonstrated that MA-ADP was a predictor for ischemic events after stent treatment. In our study, we also confirmed that clopidogrel resistance could be reflected by ADP inhibition and MA-ADP.…”
Section: Discussionmentioning
confidence: 99%